Mobile Mapping : Space, Cartography and the Digital - Wilmott, Clancy (MediaMatters., 2020)
This book presents the first in-depth discussion of how specific geographical and historical conditions shape the way in which mobile phone maps are read, deployed, and engaged with in daily life. Using a framework of mobile mapping, this concise study offers a radical analysis of the way local spatial and navigational practices are bound to global systems of knowledge and power. It argues that contemporary mobile mapping is imbued with multiple knowledges, pasts, spaces, and experiences, bringing to the fore complicated and tense relationships within cartographic and spatial assemblages. Working between media studies and geography, Clancy Wilmott underscores the transference of spatial knowledge between rational digital realms and tacit ways of understanding space and experience. Structured around a collection of seventeen interviews conducted while walking in and around Hong Kong and Sydney, Wilmott examines how potent discourses like cartographic reason continue to transform and weave through the world in ways that haunt mobile mapping, often resurrecting old conflicts in new media. In doing so, it offers an interdisciplinary rethinking of the ways in which cartographic media, urban space, and everyday knowledge is conceptualized and researched.